Biomarkers in Non-Complicated Pregnancy: Insights About Serum Myeloperoxidase and Ultrasensitive C-Reactive Protein - Kalva-Borato, Danielle C.; Ribas, Josilaine Tonin; Parabocz, Gisele Chibinski; Borba, Luciana Maria; Maciel, Margarete Aparecida Salina; Santos, Fabio André dos; Vellosa, José Carlos Rebuglio (Experimental and Clinical Endocrinology & Diabetes, 2019)
Introduction Pregnancy is characterized by increased innate immune response, with low-grade systemic inflammation. The specific role of MPO during normal pregnancy remains not well understood. Therefore, the aim of this study was to evaluate plasma levels of MPO, hs-CRP, total leukocyte, absolute neutrophil and monocyte counts, in all trimesters of normal human pregnancy compared with non-pregnant controls. In addition, possible fluctuations of MPO according to different inflammatory conditions in the normal gestation were studied.Materials and methods Case-control study (n=84) developed with 63 normal pregnant women and 21 healthy non-pregnant women. Total leukocyte, absolute neutrophils and absolute monocytes count, hs-CRP and MPO were measured in non-pregnant women and normal human pregnancy. They were evaluated according to the 3 trimesters of pregnancy and systemic low grade inflammatory status, which was identified through increased hs-CRP levels.Results MPO levels in the normal pregnant women were not elevated in every 3 trimesters of pregnancy (P=0.456) or in systemic inflammation (P=0.446). The hs-CRP levels, total leukocyte, absolute neutrophil and monocyte counts are present in higher concentrations in normal pregnant women in relation to non-pregnant women.Conclusions The MPO did not show fluctuations in plasma levels during the 3 trimesters of gestation or in relation to different inflammation conditions. Considering MPO and hs-CRP levels are changed in high cardiovascular risk conditions and MPO levels (unlike hs-CRP) didn’t increase during non complicated pregnancy, MPO could be a better biomarker than hs-CRP to monitor these patients.
Keywords: MPO; hs-CRP; biomarkers; human gestation; case-control study